THE RELATIONSHIP BETWEEN LAND USE AND LAND COVER TO RUN-OFF COEFFICIENT VALUE IN BRANTAS WATERSHED AREA, TULUNGAGUNG - EAST JAVA, INDONESIA - Bowo Eko Cahyono; Asih Sumarlin; Nurul Priyantari; Katsunoshin Nishi (International Journal of Remote Sensing and Earth Sciences, 2023)
The Ngrowo-Ngasinan sub-watershed is a part of Brantas Watershed which has an important role for the aquatic ecosystems in the Brantas watershed. Land cover changes in this sub-watershed can be identified by utilizing remote sensing technology. The use of remote sensing technology by applying Landsat 8 image data can be done by classifying several classes of land cover in the study area. Land cover affected the flow rate of a watershed because of its association with several problems due to the conversion of land. Land cover which influences the watershed ecosystems is forest. In addition to land cover, regional rainfall also affects the flow rate (runoff) in the area